Meaningful Participation in Lawmaking: A Case Study Of The 2025 TNI Law Amendment - Kurdi; R. Muhamad Ibnu Mazjah; Teuku Ahmad Dadek (Universitas Islam Negeri Alauddin Makassar, 2025)
More meaningful community participation must be applied in the preparation of laws and regulations so that the resulting legal products are responsive or autonomous. Meaningful participation is not applied in the drafting of the TNI Bill. The purpose of this research is to find out the arrangement of meaningful participation in the formation of legislation based on the PUU Law. In addition, it is also to find out the application of meaningful participation in the formation of Law No. 3 of 2025 (TNI Law). This research method is normative juridical with a statutory and conceptual approach, using legal material collection techniques with literature studies. The results showed that meaningful participation is regulated in Article 96 of the PUU Law and must be applied in the drafting of laws and regulations, including the drafting of the TNI law. However, meaningful participation has not been applied perfectly in the drafting of the TNI Law, because public participation in its drafting is still limited to hearing their opinions in public consultation activities, but the legislators do not seriously consider the opinions of civil society, and also do not provide an explanation for the reasons for not using their opinions. In addition, it is difficult for the public to access the academic papers and draft of the TNI Bill because they are not uploaded on the DPR's official website.